A Critical Review of Indonesia’s Health Law and Its Implementing Regulations: Strengths and Challenges - Puspita, Anita Arum; Maryanti, Salza Putri; Wardani, Anggun Retno; Jasinta, Indri; Stogmuller, Katharina (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2025)
This research explores the impact of Indonesia's Health Law Number 17 of 2023, particularly the removal of mandatory spending provisions and the introduction of Government Regulation Number 28 of 2024, which has led to significant public discourse. Utilizing normative legal methods with a conceptual and statutory approach, the study evaluates the alignment of these changes with the Indonesian Constitution, specifically Article 28H paragraph 1 and Article 34, as well as their compatibility with societal norms and values. The findings indicate that the abolition of mandatory spending may hinder equitable access to healthcare, despite the intention to enhance fiscal flexibility through program-based budgeting. Additionally, Article 103(4)(e) of the regulation, which addresses the provision of contraceptives for adolescents, has raised concerns due to its ambiguity and perceived misalignment with cultural and moral standards in society. This research highlights the critical need for policies that are not only legally sound but also contextually appropriate and responsive to societal needs, offering insights into the challenges of health policy reform in Indonesia.